Pelatihan Kursus Dasar Kitab Suci Bagi Orang Muda Katolik Paroki Santo Gregorius Agung Oeleta - Oktovianus Kosat; Siprianus S. Senda (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Catholics have the holy Bible as a way of life of faith. But in reality there are still many people, especially young Catholics, who do not have adequate knowledge of their own scriptures. In addition, they are not used to reading and meditating on it, let alone using the holy Bible as a source of reflection for the sake of worship. On the other hand, the need for knowledge of the scriptures is increasing among the people. Likewise, the need for skills to read and meditate on the scriptures and the ability to compose biblical reflections that are useful in thanksgiving worship. This basic course of Bible training was created to answer the needs of Catholics, especially the young Catholics in the Saint Gregory the Great Oeleta Parish. Through this activity, the participants gain knowledge about the scriptures in general, and the skills to explore the texts of the scriptures and compose biblical reflections. Keywords: Holy Bible, meditation of Bible, biblical reflection